Effect of acidic environment exposure on mechanical properties of TRM composites - Azimi, Nima (2024)
With the increasing application of textile-reinforced mortars (TRMs) for the strengthening of existing masonry structures, knowing the long-term behavior of these composites is increasingly of great importance. In recent years, there has been a progressive research effort on the durability of TRM composites following different aging protocols, yet the durability of TRMs still necessitates comprehensive experimental studies for a better understanding of their behavior. On the other hand, there is also a lack of established aging methods, including acidic attack. The present study aims to leverage knowledge of the durability of TRMs when exposed to acidic attack. For this purpose, two different commercial fabrics made of glass and basalt fibers and a lime-based mortar have been used. In parallel, two aging conditions were also investigated considering 1000, 3000, and 5000 hours of exposure. Overall, a total number of 462 specimens were tested, including tests for the matrix, fabric, and composite. Compressive, flexural, and elastic modulus tests studied the variation in the mechanical properties of mortar, tensile tests focused on the textiles, and pull-out and single-lap shear tests were used for TRM composite's behavior. To investigate possible changes in material behavior due to aging, mineralogical and chemical analysis including Optical Microscopy, SEM, XRD, and TGA were carried out.